Psychological status and role of caregivers in the neuro-rehabilitation of patients with severe Acquired Brain Injury (ABI). (5th December 2020) - Bivona, U.; Villalobos, D.; De Luca, M.; Zilli, F.; Ferri, G.; Lucatello, S.; Iannetti, M.; Cellupica, L.; Mungiello, F.; Lo Sterzo, P.; Marchegiani, V.; Puccitti, A.; et al.
ABSTRACT: Objective: To investigate the relationships between (a) the psychological status of the caregiver, (b) the specific features of caregiving as perceived by the cognitive therapist in neuro-rehabilitation, (c) the caregivers' subjective approach to neuro-rehabilitation, and (d) the functional outcome of the patient. Methods: Twenty-four patients with severe acquired brain injury and their 24 caregivers participated in this observational study. Caregivers underwent a psychological assessment examining emotional distress, burden and family strain; their subjective approach to neuro-rehabilitation has been evaluated by two specific answers. The patients' cognitive therapists responded to an ad-hoc questionnaire, namely the "Caregiving Impact on Neuro-Rehabilitation Scale" (CINRS), evaluating the features (i.e., amount and quality) of caregiving. Finally, the functional outcome of the patient was assessed through standardized scales of disability and cognitive functioning. Results: The caregivers' psychological well-being was associated to the features of caregiving, to the subjective approach to neuro-rehabilitation, and to the functional recovery of their loved ones. A better caregivers' approach to neuro-rehabilitation was also associated to an overall positive impact of caregiving in neuro-rehabilitation and to a better functional outcome of the patients. Conclusions: We posited a virtuous circle involving caregivers within the neuro-rehabilitation process, according to which the caregivers' psychological well-being could be strictly associated to a better level of caregiving and to a better functional outcome of the patients that, in turn, could positively influence the caregivers' psychological well-being. Although preliminary, these results suggest a specific psycho-educational intervention, aimed at improving the caregivers' psychological well-being and at facilitating their caring of the loved one.